Proceedings of the 4th International Conference on Wireless Mobile Communication and Healthcare - "Transforming Healthcare Thro 2014
DOI: 10.4108/icst.mobihealth.2014.257236
|View full text |Cite
|
Sign up to set email alerts
|

Wearable ECG System for Health and Sports Monitoring

Abstract: Abstract-A wireless ECG system using dry-contact electrodes is presented. The system consists of a pair of coin sized dry-contact electrodes manufactured on a standard printed circuit board that can operate both on top of the skin and through clothing and can be embedded within comfortable layers of fabric. The wireless main unit assures the transmission of the ECG signal to a computer for storage and processing. The system provides a differential gain of 56dB over a 1-150Hz bandwidth. Signals are digitized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…The wearable health monitoring systems are usually equipped with a variety of electronic and MEMS sensors, actuators, wireless communication modules and signal processing units. The measurements obtained by the sensors connected in a wireless Body Sensor Network (BSN) [ 8 , 12 , 13 , 14 ] are transmitted to a nearby processing node using a suitable communication protocol, preferably a low-power and short-range wireless medium, for example, Bluetooth [ 15 , 16 ], ZigBee [ 15 , 17 ], ANT [ 15 , 18 , 19 ] Near Field Communications (NFC) [ 20 , 21 ]. The processing node, which could be a Personal Digital Assistant (PDA), smartphone, computer or a custom made processing module based on a microcontroller or a Field Programmable Gate Array (FPGA) runs advanced processing, analysis, and decision algorithms and may also store and display the results to the user.…”
Section: Introductionmentioning
confidence: 99%
“…The wearable health monitoring systems are usually equipped with a variety of electronic and MEMS sensors, actuators, wireless communication modules and signal processing units. The measurements obtained by the sensors connected in a wireless Body Sensor Network (BSN) [ 8 , 12 , 13 , 14 ] are transmitted to a nearby processing node using a suitable communication protocol, preferably a low-power and short-range wireless medium, for example, Bluetooth [ 15 , 16 ], ZigBee [ 15 , 17 ], ANT [ 15 , 18 , 19 ] Near Field Communications (NFC) [ 20 , 21 ]. The processing node, which could be a Personal Digital Assistant (PDA), smartphone, computer or a custom made processing module based on a microcontroller or a Field Programmable Gate Array (FPGA) runs advanced processing, analysis, and decision algorithms and may also store and display the results to the user.…”
Section: Introductionmentioning
confidence: 99%
“…In that study various types of ECG devices with different electrode positions were used. The studies by Shen et al [27], and by Valchinov et al [28] reported that the ECG signal was of adequate quality during resting, walking, or jogging, but there were some small motion artefacts present during running or jumping activities. In our preliminary pilot study [18] it was shown that the particular wireless ECG body sensor can correctly detect ECG signal on a cycle ergometer; however, on the treadmill the test signal was of adequate quality for running speeds of up to 13.5 km/h, while in the presented study it was of adequate quality up to 14.96 km/h.…”
Section: Discussionmentioning
confidence: 99%
“…Daily activities using wearable monitoring devices were addressed in [33][34][35]. Furthermore, real-time activity monitoring at different premises, such as home, healthcare or sports facilities, was discussed in [155,156,199].…”
Section: Service-based Monitoring Systemsmentioning
confidence: 99%